Dynamic texture perception and oral processing of semi-solid food gels: Part 2: Impact of breakdown behaviour on bolus properties and dynamic texture perception. (July 2015) - Devezeaux de Lavergne, M.; van de Velde, F.; van Boekel, M.A.J.S.; Stieger, M.
Abstract: Food texture perception depends on food structure and oral processing behaviour. The aim of this study was to explain dynamic texture perception of emulsion-filled, semi-solid gels by properties of the boli formed during three stages of oral processing. Texture perception of emulsion-filled gels varying in fracture stress and strain was found to be a dynamic process. Specific texture attributes were perceived as dominant sensations in the beginning (firm), middle (moist, refreshing, elastic, sticky) and end of oral processing (grainy, melting, creamy). In the beginning of oral processing mechanical properties of the boli, such as first penetration peak force and flowability, were correlated to sensory firmness. In the middle of oral processing, correlations between boli properties and texture perception were more complex. Perception of moist and refreshing was related to mechanical properties of the boli, such as flowability, rather than to the amount of saliva incorporated into the boli. Perception of elastic and sticky was related to the mechanical bolus properties resilience and adhesiveness. In the end of oral processing, emulsion-filled gels were perceived either as creamy or grainy. Gels perceived as creamy revealed a high bolus flowability while gels perceived as grainy consisted of boli with a high number of broken down particles. We conclude that bolus formation and changes in the properties of the bolus underlay the changes in texture perception during oral processing. Graphical abstract: Highlights: Early texture perception correlates with fracture properties of gels. Late texture perception correlates with bolus properties of gels. Boli a high area of fragments are perceived grainy at the end of oral processing. Boli with high flowability are perceived more creamy at the end of oral processing.